Draft Genome Sequence of Frankia sp. Strain QA3, a Nitrogen-Fixing Actinobacterium Isolated from the Root Nodule of Alnus nitida - Sen, Arnab (American Society for Microbiology, 2013)

(untitled)
Members of the actinomycete genus Frankia form a nitrogen-fixing symbiosis with 8 different families of actinorhizal plants. We report a high-quality draft genome sequence for Frankia sp. strain QA3, a nitrogen-fixing actinobacterium isolated from root nodules of Alnus nitida.